2007
DOI: 10.1016/j.bbrc.2007.01.191
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton dynamics: Fluctuations within the network

Abstract: Out-of-equilibrium systems, such as the dynamics of a living cytoskeleton (CSK), are inherently noisy with fluctuations arising from the stochastic nature of the underlying biochemical and molecular events. Recently, such fluctuations within the cell were characterized by observing spontaneous nano-scale motions of an RGD-coated microbead bound to the cell surface (Bursac et al., Nature Mat. 2005;4:557-561). While these reported anomalous bead motions represent a molecular level reorganization (remodeling) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 46 publications
8
99
0
1
Order By: Relevance
“…When mean square bead displacement (MSD) was resolved as a function of time lag ⌬t, it exhibited subdiffusive behavior for small ⌬t and superdiffusive behavior for large ⌬t (Fig. 3A), confirming many previous reports (4,26,27). With increasing volume fraction, there was a dramatic reduction in spontaneous bead motions, but even at the maximum volume fraction these motions remained superdiffusive at long time scales indicating persistent nonequilibrium dynamics in the crowded intracellular space (Fig.…”
Section: Resultssupporting
confidence: 88%
“…When mean square bead displacement (MSD) was resolved as a function of time lag ⌬t, it exhibited subdiffusive behavior for small ⌬t and superdiffusive behavior for large ⌬t (Fig. 3A), confirming many previous reports (4,26,27). With increasing volume fraction, there was a dramatic reduction in spontaneous bead motions, but even at the maximum volume fraction these motions remained superdiffusive at long time scales indicating persistent nonequilibrium dynamics in the crowded intracellular space (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Newman Stephens has suggested that asthmatic airway smooth muscle demonstrates more MLCK content and activity than that of normal airways (16,17). Certainly, in addition to the contractile apparatus, the actin cytoskeleton may play a role in regulating FFIR, as suggested by Lakser and Fredberg (4,33). Also, actomyosin crossbridge Figure 2.…”
Section: Discussionmentioning
confidence: 98%
“…Herrera and colleagues have demonstrated that associated actin (32) and myosin (25)(26)(27) filaments in TSM increase in length with contraction, and dynamically shorten and lengthen with airway smooth muscle cell migration (23,24). This dynamic nature of actin filament assembly and evanescence cannot be accounted for by the actin filamentstabilizing effects of such proteins as tropomyosin (29)(30)(31) or caldesmon (33,34). Therefore, we used pharmacologic tools to test the hypothesis that altering actin dynamics and therefore actin filament length would indeed modify FFIR of contracted airway smooth muscle.…”
Section: Actin Filament Length As a Regulator Of Ffirmentioning
confidence: 99%
“…However, probe particles moving in heterogeneous active viscoelastic media can be transported in a variety of ways, so naively applying thermal fluctuation microrheology is usually inappropriate and can lead to a misinterpretation of the local mechanical properties. 8,[15][16][17][18] Over certain time scales, the MSD can sometimes be described by a time-dependent power law, 〈Δr 2 (t)〉∼t α , where the diffusive exponent, 19 α, can be related to the type of motion a particle is undergoing over a range of correlation times, t. The modes of probe motion observed are as follows: local elastic trapping (α≈0), sub-diffusion (α<1), diffusion (α=1), a combination of diffusion and convection (α>1), and ballistic motion (also known as pure convection) (α≅2). A combination of diffusion and convection can occur, for example, in thermally diffusing particles within a crawling cell.…”
Section: Particle Tracking In Living Cellsmentioning
confidence: 99%